2003
DOI: 10.1177/0890334403252475
|View full text |Cite
|
Sign up to set email alerts
|

The Baby-Friendly Hospital Initiative Increases Breastfeeding Rates in a US Neonatal Intensive Care Unit

Abstract: This study evaluated the impact of a Baby-Friendly designation on breastfeeding rates in a US neonatal intensive care unit (NICU). The medical records of all surviving infants directly admitted to the Boston Medical Center's level III, 15-bed NICU in 1995 (before Baby-Friendly policies were implemented) and 1999 (when Baby-Friendly status was granted) were reviewed. Infants receiving any breast milk by any means during the first week of enteral feeds were considered to have initiated breastfeeding. Maternal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
69
0
3

Year Published

2004
2004
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 23 publications
1
69
0
3
Order By: Relevance
“…O aumento da prevalência do aleitamento materno exclusivo por ocasião da alta hospitalar de recém-nascidos de alto risco com a implementação da IHAC está de acordo com os resultados da pesquisa realizada em Boston por Merewood et al 11 em crianças internadas também em unidade neonatal de cuidados intensivos. A proporção de crianças que recebiam leite materno exclusivo com 2 semanas de vida passou de 9,3% (1995) para 39,0% (1999) após a implementação da IHAC.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…O aumento da prevalência do aleitamento materno exclusivo por ocasião da alta hospitalar de recém-nascidos de alto risco com a implementação da IHAC está de acordo com os resultados da pesquisa realizada em Boston por Merewood et al 11 em crianças internadas também em unidade neonatal de cuidados intensivos. A proporção de crianças que recebiam leite materno exclusivo com 2 semanas de vida passou de 9,3% (1995) para 39,0% (1999) após a implementação da IHAC.…”
Section: Discussionunclassified
“…Por outro lado, em relação às informações sobre a alimentação dos recém-nascidos internados no berçário, a folha de dieta utilizada na instituição onde se realizou o presente estudo consistiu em um importante instrumento facilitador na coleta dos dados. O estudo de Merewood et al 11 também utilizou folha de registro semelhante, o que reforça a importância da realização de registros completos e legíveis e do reconhecimento da relevância destes para futuras pesquisas.…”
Section: 2unclassified
“…13 Women who deliver at hospitals that implement Baby-Friendly policies and become designated as BabyFriendly have higher breastfeeding initiation rates and longer breastfeeding duration. 40,41 In New York, no level 1 hospitals were designated as Baby-Friendly (ie, none met the certification criteria that they have implemented the Ten Steps 42 and the International Code of Marketing of Breast-milk Substitutes 43 ). 44 However, 55% (N = 27) of level 1 hospitals had low 7 Null models contained only hospital-specific random intercepts and no independent variables.…”
Section: Discussionmentioning
confidence: 99%
“…3 A number of studies have been conducted to evaluate the implementation and effectiveness of the Baby-Friendly Initiatives in the United States, and they found that full implementation of Baby-Friendly policies was associated with increased breastfeeding rates. [4][5][6] Although there have been increases in the total number of Baby-Friendly designated hospitals in the United States, evaluation studies also indicate challenges with implementing Step 10-foster the establishment of breastfeeding support groups and refer mothers to them on discharge from the hospital or birth center. [7][8][9] The challenges most frequently reported with implementing this step included hospitals not facilitating peer counseling for breastfeeding mothers, lack of referral systems to other agencies that provide postpartum breastfeeding support, and hospitals not having control of the services outside of the hospital.…”
Section: Guest Editorialmentioning
confidence: 99%